New Media New Society? - Senturk, Murat; Ragnedda, Massimo; Muschert, Glenn (Istanbul University Press, 2023)
This edited book is a collection of nine chapters which include topics and issues like toy activism, WhatsApp groups, online dating sites, migrants and social media, activism and social media, artificial intelligence and/in journalism, virtual ethnography, subculture practices in social media and new audiences in new media like binge-watchers. All these topics represent different forms of multimedia cultures, and mostly the emphasis is on the daily practices occurred in social media. This edited book shows us how the convergence phenomenon occurs nowadays. Toyification of society as an expressive media for communication and cooperative play, not just for children and teenagers but also for adults, as part of produsage and affectionate activism. We used to think of the convergence factor in medium, platforms, etc. However, this book reminds us that as new media cultures expand, we should also consider the convergence of different segments of society. In that sense, it also focuses on mediums (like smartphones) and activities and agents. As McLuhan highlights, we encounter these items like mobile phones in every part of everyday life, which turn out to be an extended part of our bodies. Besides, we produce relationships and communities via these items and applications on it, and day by day, these items and applications have become a trend in almost every culture and society. This 'we' composition may also differ, like university students, women, elderly people, etc. However, with users and applications as an ecosystem, it may sometimes (re) produce unequal relationships, especially on gender-based activities and representations.